The Influence of Sex-role Self-Concept on Academic Performance among Secondary School Students in Kenya (Global Journal of Human-Social Science, 2015)
The study examined the influence of sex-role selfconcept on academic performance among students in coeducational secondary schools in Siaya District. The sample comprised 154 boys and 89 girls in Form 3. Bem's Sex-role Inventory (BSRI) was used to collect data on masculinity and femininity while students' academic scores were obtained from school records. Linear Regression analysis revealed that sex-role self-concept predicts academic performance. Sex-role self-concept also explained significant variance in academic scores. The results further showed significant difference between the academic mean scores of androgynous, masculine, feminine, and undifferentiated students. However, the androgynous students had better academic mean score than the other students. The results support the view that sex-role selfconcept is a predictor of achievement than gender.
Keywords: collect data on masculinity and femininity while students’ academic scores were obtained from school records